Policy Awareness, Current Practices, and Barriers: A Proposed Upskilling to Special Education Teachers and Receiving Teachers towards Culture of Inclusivity - Garcia, Arlene (JPAIR Multidisciplinary Research, 2023)
This study presents a comprehensive analysis of key aspects related to the distribution of Special Education Teachers (SPET) and receiving teachers, their awareness of inclusive education policies, their practices, and the barriers they face. Data collected from diverse educators shed light on age, gender, teaching experience, specialization, policy awareness, and inclusive practices. The study highlights the diverse age distribution among teachers handling the SPED program. Furthermore, it points out the prominence of female teachers in the workforce. A significant proportion of teachers possess limited teaching experience and a limited number of specialized SPED teachers. Regarding policy awareness, both Special Education Teachers (SPET) and receiving teachers clearly understand inclusive education policies. Inclusive practices among teachers were consistently observed, especially in admission, teaching, and modifying learning packages for learners with special needs. Identifying the lack of training as a major barrier in IE, there is a necessity for professional development to support effective inclusive practices. The findings underscore vital family support services, parental engagement in decision-making, and collaborative opportunities. Based on the findings, the researcher recommends targeted professional development for teachers, awareness campaigns on Indigenous Peoples' rights, encouraging specialization in SPED, strengthening collaboration, and expanding effective practices like the "Child Find" approach.
Keywords: policy awareness; receiving teachers; special education teacher; special education; descriptive; Philippines